2021
DOI: 10.3390/jcm10040803
|View full text |Cite
|
Sign up to set email alerts
|

Modifiable Psychological Factors Affecting Functioning in Fibromyalgia

Abstract: Objective: To examine the role of several interrelated, potentially modifiable psychological factors (i.e., mindfulness and catastrophizing) in influencing patient-reported functioning. Methods: In this cross-sectional study, 107 patients with fibromyalgia completed self-report assessments of pain severity, functioning and impact of symptoms, mindfulness, and pain catastrophizing. Linear regression and bootstrapping mediation analyses were performed to assess the relationships between these factors. Results: P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 50 publications
0
20
2
Order By: Relevance
“…Research has repeatedly shown that pain catastrophizing and pain acceptance are important predictors of self-reported physical functioning in samples with acute [ 104 , 105 ] and chronic pain [ 105 , 106 ], including FM [ 41 , 107 , 108 , 109 , 110 ]. Our findings are consistent with the previous evidence.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Research has repeatedly shown that pain catastrophizing and pain acceptance are important predictors of self-reported physical functioning in samples with acute [ 104 , 105 ] and chronic pain [ 105 , 106 ], including FM [ 41 , 107 , 108 , 109 , 110 ]. Our findings are consistent with the previous evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Pain catastrophizing has been observed in individuals with FM [ 40 ] and has been robustly associated with physical impairment in FM and other pain conditions [ 41 , 42 , 43 , 44 ]. However, the role of pain catastrophizing in individuals with chronic pain conditions and comorbid obesity remains less clear.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pain is the most common complaint in these patients; most patients present with vague, diffuse pain and nonspecific muscle pain. Accompanying symptoms such as morning dryness, fatigue and headache are also common (12). The risk is higher in women than men and increases with age, such that it reaches its maximum at the age of 55 -79 (13).…”
Section: Contextmentioning
confidence: 99%